PENGEMBANGAN BUKU BHINEKA NUSWAPADA MODEL POP-UP SEBAGAI MEDIA PEMBELAJARAN LEGENDA INDONESIA - Putri, Agustiani (Universitas Insan Budi Utomo, 2020)
Nowadays, most teenagers don't like Indonesian legends because they are considered as old-fashioned and boring stories. The results of a survey of 124 respondents who are teenagers resulted in 85% of respondents consider the legend is not interesting. Whereas 10% of respondents answered interestingly and 5% answered relatively. This study aims to: (i) develop pop-up books that present Indonesian legends for junior high school students, (ii) provide unique and interesting short stories and (iii) illustrate the comparison of student responses before and after using pop-up books as an alternative learning medium. The research method is research and development (R&D). Based on the results of this study, it was concluded that (1) this research produced a product in the form of a pop-up book entitled